Research progress on digestive disorders following traumatic brain injury - Lin, Yongshuang; Hou, Chengshan; Wang, Cheng; Chen, Rui; Zhu, Yunzhong; Zhou, Qing; Shao, Binbin; Huang, Yi; Li, Shun (Frontiers in Immunology, 2024)
Traumatic brain injury (TBI) is a prevalent disease that poses a significant threat to global public health. Digestive dysfunction, as a common complication, is of particular importance to understand its pathogenesis, diagnostic criteria, and relevant treatment strategies. TBI can affect digestive function through inflammatory immune responses, the enteric nervous system, and hormonal levels. Furthermore, TBI can also impact neurologic recovery through bidirectional communication along the brain-gut axis. Therefore, this article aims to summarize the underlying mechanisms and further explore individualized feeding strategies, therapeutic approaches, long-term prognosis for TBI patients, as well as recent advancements in related technologies. Further understanding of the pathogenesis of digestive system dysfunction after TBI on the basis of the interaction of gut-brain axis is conducive to more future therapies to treat TBI and improve the long-term prognosis of patients through improving digestive function, and achieve good clinical efficacy.